The evolvement of session design from junior age to senior peak performance in world-class cross-country skiers - Walther, J.; Haugen, T.; Strøm Solli, G.; Tønnessen, E.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2024)
Purpose To compare designs of training sessions applied by world-class cross-country skiers during their most successful junior and senior season.